Evaluation of financial strength of joint venture commercial banks and domestic commercial banks in nepal: using camels framework (The International Research Journal of Management Science, 2022)
This study aims to compare the financial strength of joint venture and domestic commercial banks in Nepal using data from mid-July 2011/2012 to mid-July 2019/2020. The financial strength analysis is based on the CAMELS (capital adequacy, asset quality, management quality, earning performance, liquidity, and sensitivity to market risk) framework. A descriptive research design has been used. This paper finds that Nepalese joint venture banks are financially sound with higher asset quality, management quality, earning performance, and liquidity than Nepalese domestic banks. Nepalese joint venture banks can cash in on higher IT infrastructure or better investment culture from its foreign collaboration and thus perform better compared to domestic commercial banks.